Financial Literacy of Generation Z in The Workplace: Between Savings, Investment, And Consumerism (A Case Study of PT Andaru Sakra Karsa) - Silaban, Supriska; Widodo , Sri (Dinasti International Journal of Management Science, 2025)
Generation Z, generally defined as those born between 1997 and 2012, is entering the workforce and bringing unique characteristics in financial management. This study aims to analyze the level of financial literacy among Generation Z employees at PT Andaru Sakra Karsa and to explore their financial behavior related to savings, investment, and consumerism. The research method employed was a quantitative approach, with a questionnaire distributed to Generation Z employees at PT Andaru Sakra Karsa. Data analysis was conducted using descriptive and inferential statistics. The results showed that the level of financial literacy among Generation Z employees at PT Andaru Sakra Karsa was in the moderate category. Their saving behavior was relatively good, but their understanding and participation in investment were still low. On the other hand, there was a high tendency toward consumerism, mainly driven by social media influence and easy access to credit. This study concludes that comprehensive and sustainable financial education programs in the workplace are crucial to improve Generation Z's financial literacy, encourage healthy financial behavior, and prepare them to face future financial challenges.